Role of molecular breeding in understanding salinity tolerance in cotton: limitations and perspectives - Shicong WANG; Meiling HOU; Hadiqa HASSAN; Fatima M. ABBAS; Zehbah A. AL AHMAD; Sameer H. QARI; Nurul A.B. HANIFAH (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Cotton is a significant fiber crop globally and has a considerable share in many countries’ gross domestic product (GDP). It is the most critical contributor to the textile industry and provides income to millions of farmers. Salt stress is abiotic stress, decreasing the cotton yield on a large area. Salt stress is a polygenic trait, and cotton’s response to salt stress involves a complex gene pathway. Breeders have been breeding novel salt-tolerant cotton genotypes for decades to sustain their growth on salt-affected soils. In recent years, cotton breeders have employed several breeding tools like hybridization, backcrossing, and mass selection to develop tolerant genotypes. Still, due to several limitations, these techniques are being replaced by novel molecular breeding tools. With the advancement in molecular breeding, the speed to improve crop tolerance to salt stress has been increased. Quantitative trait loci (QTL) mapping, genome-wide association studies (GWAS), transcription factors (TFs) analysis, and transcriptome have identified several genomic regions for salinity tolerance in cotton. At the same time, genetic engineering and clustered regularly interspaced short palindromic repeats (CRISPR/Cas9) led to the development of salt-tolerant cotton cultivars. Genetic engineering is key in breeding transgenic cotton cultivars resistant to multiple abiotic stresses. CRISPR/Cas9, a new gene manipulation technique, is used to edit the genes for salt tolerance in cotton without any biological barrier. CRISPR/Cas9 could be a more powerful tool to manipulate the desired cotton genome against salinity tolerance. These research and breeding tools have been successfully used in genetic research and breeding for drought tolerance in cotton. This unique review presents a full overview of the use of different molecular tools and their role in enhancing salt tolerance in cotton. Using this information, cotton breeders can understand the salinity tolerance mechanism in cotton by choosing the most reliable genetic breeding tool.